Design of a business readiness model to realise a green industry 4.0 company. Issue 9 (2nd September 2021) - Benešová, Andrea; Basl, Josef; Tupa, Jiří; Steiner, František
ABSTRACT: The paper reports research on the implementation of green aspects into the latest industrial revolution called Industry 4.0 and proposes the design of a business readiness level model for Industry 4.0. The analysis is based on the available maturity models for Industry 4.0, which are investigated to determine whether and to what extent they fulfil the 'green' trends by their name, content or specialized dimensions. This analysis was initiated over recent years, by a strong interest in integrating the elements and principles of Industry 4.0 into enterprises, together with an increased interest in achieving carbon neutral production and society in the coming decades, including recent EU Green Deal documents. The first part of the paper describes the basic requirements of the Industry 4.0, new digital strategies and green agreements. The major parts of the paper provide an analysis of current maturity and readiness models for Industry 4.0 together with specification, design and development of a readiness model for companies to implement Industry 4.0 with respect to green aspects. The final part of the paper provides an evaluation based on questionnaire survey with discussion, conclusions and avenues for future research.